A quasi-lagrangian diagnostics investigation of rapid cyclogenesis in a polar air system - Cook, William A. (Monterey, California. Naval Postgraduate School, 1983)
A synoptic investigation employing quasi-Lagrangian diagnostic techniques was conducted for a North Atlantic Ocean polar flow undergoing a period or rapid cyclogenesis. The polar flow was of relatively small horizontal scale and developed in a region of low static stability and large low-level baroclinity, which is consistent with theoretical studies. Rapid surface pressure falls and vigorous circulation increases correlate well with the observed maxima in low-level inward mass transport and upper-level mass outflow, and are temporarily coincident with the incursion of to forward divergence quadrant of a jet streak into the budget volume. The most rapid increases of absolute vorticity occurred in the 250 to 300 mb layer, and are related to combined contributions of positive vorticity advection and vertical redistribution processes. The dominant forcing of low-level absolute vorticity increases comes primarily from the divergence source term. Approved for public release; distribution is unlimited. Lieutenant, United States Navy http://archive.org/details/aquasilagrangidi1094519963